Experimental static and dynamic response of RC beams damaged and strengthened with NSM GFRP rod. (1st June 2020) - Capozucca, R.; Magagnini, E.; Vecchietti, M.V.
Abstract: Inserting FRP rods into grooves using the NSM technique has been demonstrated to be a suitable method for repairing reinforced concrete (RC) beams. There is limited experience with the use of GFRP in the strengthening of RC elements due to low Young's modulus of glass fibers. The aim of the paper is to analyse the static and dynamic behaviour of RC beams damaged and strengthened by glass fiber reinforced polymer (GFRP) rods utilizing the near surface method (NSM) . Undamaged and damaged three RC beams have been experimentally tested under bending loading with and without strengthening by GFRP rods. For a beam, damage has been represented firstly by notches on concrete cover. The beam has been successively strengthened by epoxy resin and NSM GFRP rod and then subjected to bending tests. Vibration tests have been adopted as nondestructive method of control during the experiments to assess the response of RC beams at different damage steps of concrete or due to decrease of bond of GFRP rod. Vibration tests foresaw two boundary conditions, respectively, free-free and hinged ends. Experimental static and vibration results are below shown; discussion and comments on the strengthening bond of NSM GFRP rod have been developed.